2009
DOI: 10.1007/s12600-009-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of melon bacterial blotch by plant beneficial bacteria

Abstract: Plant beneficial bacteria (PBB) have shown potential for disease control and are particularly important in the management of bacterial diseases, which are poorly controlled by conventional methods. In melon, bacterial fruit blotch caused by Acidovorax citrulli is a seedborne disease that is particularly destructive under certain conditions. PBB strains were screened for their ability to protect seeds and leaves from bacterial fruit blotch, and their antibiosis activity and plant colonization were studied. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
0
10
0
4
Order By: Relevance
“…Biological control has been previously explored for BFB management (9,25,41). Fessehaie and Walcott (9) demonstrated that seed treatments with A. avenae (formerly A. avenae subsp.…”
mentioning
confidence: 99%
“…Biological control has been previously explored for BFB management (9,25,41). Fessehaie and Walcott (9) demonstrated that seed treatments with A. avenae (formerly A. avenae subsp.…”
mentioning
confidence: 99%
“…Mengulluoglu and Soylu (2012) showed that thyme and origanum essential oils inhibited Acidovorax citrulli population in in vitro petri assays. Fessehaie and Walcott (2005), Oliveira et al (2006), Medeiros et al (2009), andWang et al (2009) indicated that using antagonistic bacteria or yeasts is promising to manage bacterial fruit blotch disease. Our ongoing studies will be focused on the determination of Acidovorax citrulli isolates from infected watermelon and melon in the nurseries or fields in order to reveal the genetic relationships, epidemiology of the disease in the region, and to propose the disease management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 208 endospore-forming isolates from rhizospheric soil and 153 from root endophytes were obtained in this study. Additionally, the bacterial isolate Paenibacillus lentimorbus MEN2 obtained from roots of Cucumis melo by Rosa Mariano was included in our screening 16 as well as six other strains from our collection that were efficient in other experiments.…”
Section: Screening Bacterial Isolatesmentioning
confidence: 99%